Regulation of metabolic homeostasis by the TGF‐β superfamily receptor ALK7 - Ibáñez, Carlos F. (The FEBS journal, 2022)
ALK7 (Activin receptor‐like kinase 7) is a member of the TGF‐β receptor superfamily predominantly expressed by cells and tissues involved in endocrine functions, such as neurons of the hypothalamus and pituitary, pancreatic β‐cells and adipocytes. Recent studies have begun to delineate the processes regulated by ALK7 in these tissues and how these become integrated with the homeostatic regulation of mammalian metabolism. The picture emerging indicates that ALK7’s primary function in metabolic regulation is to limit catabolic activities and preserve energy. Aside of the hypothalamic arcuate nucleus, the function of ALK7 elsewhere in the brain, particularly in the cerebellum, where it is abundantly expressed, remains to be elucidated. Although our understanding of the basic molecular events underlying ALK7 signaling has benefited from the vast knowledge available on TGF‐β receptor mechanisms, how these connect to the physiological functions regulated by ALK7 in different cell types is still incompletely understood. Findings of missense and nonsense variants in the Acvr1c gene, encoding ALK7, of some mouse strains and human subjects indicate a tolerance to ALK7 loss of function. Recent discoveries suggest that specific inhibitors of ALK7 may have therapeutic applications in obesity and metabolic syndrome without overt adverse effects. ALK7 is a member of the TGF‐β receptor superfamily predominantly expressed by cells and tissues involved in endocrine functions. ALK7’s primary function in metabolic regulation of energy stores is to limit catabolic activities by antagonizing pathways of lipid and amino acid degradation. In white adipose tissues, ALK7 signaling suppresses beta‐adrenergic receptor expression and function in response to nutrient overload, resulting in reduced mitochondrial biogenesis, lipolysis, and lipid oxidation.